Hubungan Komunikasi Interpersonal, Motivasi Kerja, Efikasi Diri dan Budaya Organisasi pada Peningkatan Kinerja Pegawai Badan Pengelola Pajak dan Retribusi Daerah Kota Medan - Annisha Suvero Suyar (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2021)
The effect of interpersonal communication, motivation, self-efficacy and organizational culture on employee performance at the Medan City Tax and Retribution Management Agency partially. The total population in this study amounted to 249 people, and using the Slovin formula obtained a sample of 153 people. The analysis technique used is multiple linear regression. The results showed that self-efficacy had a significant effect on the employee performance in the Medan City Regional Tax and Retribution Management Agency. Interpersonal communication has a significant effect on the employee performance in the Medan City Regional Tax and Retribution Management Agency. Motivation has no effect on employee performance at the Medan City Regional Tax and Retribution Management Agency. Organizational Culture has a significant effect on employee performance at the Medan City Regional Tax and Retribution Management Agency. Teamwork has no effect on the performance of agencies in the Medan City Regional Tax and Retribution Management Agency.